1984
DOI: 10.3109/00016348409157126
|View full text |Cite
|
Sign up to set email alerts
|

Atenolol and Metoprolol. A Comparison of Their Excretion into Human Breast Milk

Abstract: The transfer of atenolol and metoprolol to human breast milk was studied in 7 lactating women with hypertension. Concentrations of atenolol and metoprolol in maternal plasma and milk and in plasma of the nursed infants were determined. Blood samples were obtained from the women and from the infants during a dose interval. Milk was collected repeatedly from the left breast but only twice from the right breast. The ratio between the area under the milk concentration versus time curve (AUCm) and the area under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Comparison with data for other [3-blockers indicates a higher milk/blood ratios (2.5-10) for acebutolol and a similar value (1.6-4.5) for atenolol, metoprolol, oxprenoloi and propranolol (Boutroy et al 1986;Kulas et al 1984;Liedholm et al 1981;Lundborg et al 1981;SandstrOm and Regardh 1980;Sioufi et al 1984;Thorley et al 1983;White et al 1984).…”
Section: Discussionmentioning
confidence: 97%
“…Comparison with data for other [3-blockers indicates a higher milk/blood ratios (2.5-10) for acebutolol and a similar value (1.6-4.5) for atenolol, metoprolol, oxprenoloi and propranolol (Boutroy et al 1986;Kulas et al 1984;Liedholm et al 1981;Lundborg et al 1981;SandstrOm and Regardh 1980;Sioufi et al 1984;Thorley et al 1983;White et al 1984).…”
Section: Discussionmentioning
confidence: 97%
“…101 As infant plasma concentrations are negligible, use during breastfeeding is not expected to pose a risk to the infant. 115,116 Although symptoms caused by β-blockade (such as brady cardia and hypoglycaemia) have not previously been reported following exposure to propranolol or metoprolol via milk, some authors nevertheless recommend that exposed infants should be closely observed for these signs. 117 Even though such effects perhaps could be an issue in preterm infants or newborns, we consider it unlikely that any such pharmacological effect would arise in a breastfed infant.…”
Section: Ergot Alkaloidsmentioning
confidence: 96%
“…However, the extent of such an increase is variable among the various drugs: it ap pears quite high with OH-metoprolol, mod erate for diacetolol, and minimal for betaxo- [32].…”
Section: Commentsmentioning
confidence: 99%
“…Effective concentrations capable of re ducing heart rate and arterial blood pressure have been noticed in about 35% of the stud ied population 24-36 h after birth [30], Milk atenolol levels, in the cases tested so far, are considerably higher (up to 5-fold) than those present in maternal plasma and the risk of effective intake by breast-fed neo nates does exist [31][32][33]. It should also be mentioned that in those cases where the treatment to the mother was stopped 24 h before delivery, no atenolol could be mea sured in the umbilical cord or in the new born [27,28].…”
Section: Atenololmentioning
confidence: 99%
See 1 more Smart Citation